Genome-Wide Identification and Expression Pattern Analysis of the HAK/KUP/KT Gene Family of Cotton in Fiber Development and Under Stresses - Yang, Xu; Zhang, Jingjing; Wu, Aimin; Wei, Hengling; Fu, Xiaokang; Tian, Miaomiao; Ma, Liang; Lu, Jianhua; Wang, Hantao; Yu, Shuxun (Frontiers in Genetics, 2020)
The potassium transporter family HAK/KUP/KT is a large group of proteins that are important in plant potassium transport and plays a crucial role in plant growth and development, especially in economic crops. Although HAK/KUP/KT genes have been identified in many species, research on these genes in cotton is still quite rare. In this study, in total, 21, 24, 45, and 44 HAK/KUP/KT genes were identified in Gossypium arboreum, Gossypium raimondii, Gossypium hirsutum, and Gossypium barbadense, respectively. Phylogenetic analysis showed that these genes were divided into four clusters. The G. hirsutum gene promoters contained diverse cis-regulatory elements, such as drought-responsive elements, low temperature-responsive elements, and other elements. The RNA-seq data and qRT-PCR results showed that HAK/KUP/KT genes had different expression patterns in fiber development. The qRT-PCR results of drought and NaCl treatment indicated that HAK/KUP/KT genes might play important roles in abiotic stress responses. These results will provide molecular insights into potassium transporter research in cotton.